Diagnosis of the methods used for teaching english grammar in the Advanced English I courses during the second semester –2012 at the Foreign Languages Department of the University of El Salvador - Candelario López, Iván Alcides; Martínez Peñate, Geraldinee Karen Kiev; Rivas Sandoval, Karla Sofía; Vásquez Hernández, Marcela Carolina; Franco Ramos, Rhina (San Salvador, El Salvador : Universidad de El Salvador, 2014)
This work is divided in two main parts a bibliographical part and a small field research to contrast the theory with the practice. The bibliographical research includes information related to what some authors say about different methods and approaches for teaching grammar. On the other hand, the small field research consisted on finding out if the methods proposed by experts were being used by professors working at the FLD and if so, to what extent they were being used. As stated before, there are different methods for teaching grammar to learners of English as a second language or a foreign language. Among those methods proposed by experts there can be mentioned the following: Presentation Practice and Produce (PPP), Error Correction, Consciousness Raising and The Grammar Translation Method. These methods can be classified within two approaches depending on the way grammar is taught; that is so say, inductively or deductively. They are said to be deductive when the grammatical structures or rules are dictated to the students first (Rivers and Temperley 110). In other words learners are directly exposed to grammar rules. On the other hand, there is the inductive approach, which represents a more modern style for teaching grammar. In this approach the new grammatical structures or rules are presented to learners in a real language context (Goner, Phillips, and Walters 135) The methods under study were the grammar translation methods; presentation practice and produce, consciousness raising method and error correction; all these were related to one of the main approaches for teaching grammar, inductive and deductive approaches. The methods related to inductive grammar teaching are grammar translation method and error correction. They are said to be deductive because grammar rules are explicitly studied. The others are considered inductive methods as the cases of presentation practice and produce and consciousness raising because they give several examples of a structure without mentioning the rules; in this case students guess the rule.
Incluye anexos.
Tesis para optar al título de -- (Licenciado en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2014
Bibliografía : hojas 45-46
Audiencia general
Texto en inglés.
Keywords: Métodos de enseñanza; Lenguaje y lenguas -- Enseñanza; Enseñanza de la gramática inglesa